A morphometric study of the celiac trunk and review of the literature. Issue 6 (7th August 2012) - Venieratos, Dionysios; Panagouli, Eleni; Lolis, Evangelos; Tsaraklis, Athanasios; Skandalakis, Panagiotis
<x xml:space="preserve">Abstract</x> The anatomy of the celiac trunk and its branches was examined in 77 adult human cadavers of Caucasian (Hellenic) origin. The celiac trunk followed the normal pattern, namely trifurcation to the common hepatic, splenic, and left gastric arteries, in 90.9% of the dissections (70/77). Two different types of trifurcation were observed: (a) a true tripod when the celiac trunk ended in a complete trifurcation (74.0%, 57/77) and (b) a false tripod when the three arteries did not have a common origin (16.9%, 13/77). Such a clear predominance of the true tripod is not reported elsewhere. Anatomic variations were found in 9.1% (7/77). Bifurcation of the celiac trunk into splenic and left gastric artery (splenogastric trunk) was observed in one specimen (1.3%), whereas the common hepatic artery emerged directly from the aorta. Absence of the celiac trunk was also found in two individuals (2.6%). The celiac trunk presented additional branches (lumbar and inferior phrenic arteries) in 5.2% (4/77). The median level of origin of the celiac trunk was at the upper third of L1 (22.7% to 17/75). The total length of the celiac trunk ranged from 1.1 to 5.0 cm, whereas the mean length was 2.8 cm (standard deviation = 0.80 cm, standard error of mean = 0.09 cm) irrespective of the existence of variations. The mean length of the celiac arteries which formed a false tripod was found to be larger than those of the arteries which formed a true tripod but only a weak statistically significant difference was established (P = 0.073). Clin. Anat. 26:741–750, 2013. © 2012 Wiley Periodicals, Inc.